The Cambridge companion to world literature - Etherington, Ben; Zimbler, Jarad (Cambridge companions to literature, 2018)
The Cambridge Companion to World Literature introduces the significant ideas and practices of world literary studies. It provides a lucid and accessible account of the fundamental issues and concepts in world literature, including the problems of imagining the totality of literature; comparing literary works across histories, cultures and languages; and understanding how literary production is affected by forces such as imperialism and globalization. The essays demonstrate how detailed critical engagements with particular literary texts call forth differing conceptions of world literature, and, conversely, how theories of world literature shape our practices of readings. Subjects covered include cosmopolitanism, transnationalism, internationalism, scale and systems, sociological criticism, translation, scripts, and orality. This book also includes original analyses of genres and forms, ranging from tragedy to the novel and graphic fiction, lyric poetry to the short story and world cinema